Evaluation of the Quality of Life in Moroccan Patients Diagnosed with Hypoparathyroidism - Mohammed-Amine Essafi; Samira Handa; Hayat Aynaou; Houda Salhi (International Journal of Endocrinology)
Objective. Hypoparathyroidism (HPt) is a rare endocrine disorder often of postsurgical origin, resulting in hypocalcaemia. Several complications have been described including impairment of quality of life (QoL). Our study aims to evaluate the effect of hypoparathyroidism on the QoL of patients diagnosed with HPt. Methods. A cross-sectional study was conducted in the Department of Endocrinology, Diabetology, Metabolic Diseases and Nutrition of the Hassan II University Hospital of Fez. We included in our study all patients followed for chronic HPt. Well-being was assessed using the WHO 5 index, and QoL was assessed by the SF-36 questionnaire in its validated Arabic version. Data were entered into Excel and analysed using SPSS 26. Multiple linear regression was utilized to ascertain the variables linked to the QoL in individuals diagnosed with HPt. Results. A total of 143 patients with HPt were included in the study, 86.7% of whom were female. The mean age of the patients was 44.6 ± 17.3 years. 89.9% were of postsurgical etiology. The assessment of well-being by the WHO 5 index showed a low score (<50), meaning poor well-being in 44.8%. Regarding the QoL, the assessment showed low scores in the areas of general health (41.7), limitations due to physical condition (40.5), vitality (41.4), and limitations due to psychological condition (42.6). The multiple linear regression model revealed a noteworthy association between low SF-36 score and advanced age (β = −5.91; p<0.001), surgical etiology (β = 8.71; p<0.001), low education level (β = −10.1; p<0.001), and poor compliance with medication (β = −11.3; p<0.001). However, the relationship between impaired QoL and achievement of normocalcemia was nonsignificant (p=0.69). Conclusions. Our work objective is that patients with HPt have a reduced and multifactorial QoL. Despite normocalcemia, it is hypothesized that parathyroid hormone directly influences QoL. These results could serve as a basis for future research.